Declines in mitochondrial respiration during cardiac reperfusion: Age-dependent inactivation of α-ketoglutarate dehydrogenase - Lucas, David T. (The National Academy of Sciences, 1999)
We previously reported that cardiac reperfusion results in declines in mitochondrial NADH-linked respiration. The degree of inactivation increased with age and was paralleled by modification of protein by the lipid peroxidation product 4-hydroxy-2-nonenal. To gain insight into potential sites of oxidative damage, the present study was undertaken to identify specific mitochondrial protein(s) inactivated during ischemia and reperfusion and to determine which of these losses in activity are responsible for observed declines in mitochondrial respiration. Using a Langendorff rat heart perfusion protocol, we observed age-dependent inactivation of complex I during ischemia and complex IV and α-ketoglutarate dehydrogenase during reperfusion. Although losses in complex I and IV activities were found not to be of sufficient magnitude to cause declines in mitochondrial respiration, an age-related decrease in complex I activity during ischemia may predispose old animals to more severe oxidative damage during reperfusion. It was determined that inactivation of α-ketoglutarate dehydrogenase is responsible, in large part, for observed reperfusion-induced declines in NADH-linked respiration. α-Ketoglutarate dehydrogenase is highly susceptible to 4-hydroxy-2-nonenal inactivation in vitro. Thus, our results suggest a plausible mechanism for age-dependent, reperfusion-induced declines in mitochondrial function and identify α-ketoglutarate dehydrogenase as a likely site of free radical-mediated damage.